OPTIMIZATION OF GEOPOLYMERS BUILDABILITY FOR CONSTRUCTION 3D PRINTING - Temirzakuly, Bakbergen (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This study explores the development of a 3D-printable geopolymer paste using locally available raw materials like calcined clay, fly ash, and ground granulated blast furnace slag (GGBS). The research aimed to optimize the material composition for structural strength, extrudability, and buildability with adequate mechanical performance for construction applications. A systematic approach was followed, involving X-ray fluorescence (XRF) and X-ray diffraction (XRD) analyses for the characterization of the precursor materials, which indicated the presence of a high content of SiO₂ (77.69%) in the calcined clay owing to quartz impurities. A range of geopolymer mixes was tested systematically, and Mix B14 emerged as the optimum composition. The mix design utilized an adjusted alkali activator ratio (NaOH:Na₂SiO₃ = 1:2) to improve mechanical performance over an extended period. Mechanical testing indicated that B14 had a 28-day compressive strength of 23.92 MPa and flexural strength of 6.74 MPa, demonstrating improved strength retention compared to the earlier formulations. The dimensional accuracy study also confirmed that the wall thickness deviation and layer height variation were within acceptable levels, ensuring both printability and structural stability. Strength tests on printed samples showed a 30% decrease in comparison to molded samples, although the small difference in flexural strength along and perpendicular to layers indicated excellent interlayer adhesion. The results corroborate that B14 is an effective formulation for large-scale 3D printing in construction, a sustainable and contextually responsive solution compared to traditional cement-based materials. The next stage of research should involve durability testing, shrinkage testing, and large-scale testing to further develop the material's potential in additive manufacturing for sustainable infrastructure development.
Keywords: Geopolymer; Construction 3D printing; Buildability; Extrudability; type of access: embargo